INFLUENCE OF A PREPARATION TRAINING FOR STUDENT COMPETENCY COMPETITIONS IN CAD MECHANICAL - Ardianto, Fiki; Subandi, Subandi; Jarwopuspito, Jarwopuspito; Efendi, Yosep (Jurnal Dinamika Vokasional Teknik Mesin, 2023)
Lomba Ketrampilan Siswa (LKS) is an annual activity in student competency competition among students at the Vocational High School (VHS) [R1] level in accordance with the areas of expertise taught at each participant's school. This activity is one part of a series of selections to get the best students from all over Indonesia who will be guided by teams in their respective areas of expertise and included in international level competency competencies. Students who take part in the LKS competition are students who are chosen by their school. To get the title of champion, of course, there is a lot of preparation that must be undertaken and one of them is training. This study aims to present data regarding the training program that students undergo as preparation for regional-level LKS competitions. This research uses a qualitative approach with a descriptive research type. The results of this study found that there were several scheduled, independent and incidental training programs